MENCARI ALAS AKAR KONFLIK PERTANAHAN: SUATU TINJAUAN DINAMIKA MASYARAKAT PEDESAAN DI JAWA - Matua Sihaloho (Jurnal Agrisep)
Agrarian conflicts are one of agrarian facts and also become the popular ‘main theme’ in many discussions and studies in Indonesia. Cases and studies of land and sea agrarian source are the two important agrarian objects, for their connection to dominant source for many sides involved. The reality that happened on the natural/agrarian source management is one of the aspects that can make village society more dynamics, both in Java and outside Java. This writing tries to assess how conflicts among sides and the impacts on social life, especially in society development dynamic review. Some basic root of agrarian conflicts are society access level to land, regulations and outsider programmes, the fading of local institutions, threat to society existence, and other things that connecting to local institutions.